Prophetic Leadership: The Leadership Model of Prophet Muhammad in Political Relation of Social – Ummah - El Syam, Robingun Suyud (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The leadership practiced by the Prophet Muhammad in the early days of Islam's birth in Madinah was a prototype of the next Muslim leadership. Therefore, it is not excessive to say that leadership in Muhammad as the bearer of Islamic mission is the masterpiece of Muhammad the founder of the foundations of Islamic leadership, which can make Madinah labeled al-Qur'an as,